A Values-Affirmation Intervention Does Not Benefit Negatively Stereotyped Immigrant Students in the Netherlands - de Jong, Elisabeth M.; Jellesma, Francine C.; Koomen, Helma M. Y.; de Jong, Peter F. (Frontiers in Psychology, 2016)
Previous research showed that a values-affirmation intervention can help reduce the achievement gap between African American and European American students in the US. In the present study, it was examined if these results would generalize to ethnic minority students in a country outside the US, namely the Netherlands, where there is also an achievement gap between native and ethnic minority students. This type of intervention was tested in two separate studies, the first among first-year pre-vocational students (n = 361, 84% ethnic minority), and the second among sixth grade students (n = 290, 96% ethnic minority). Most minority participants had a Turkish-Dutch or Moroccan-Dutch immigrant background. In the second study, a third condition was added to the original paradigm, in which students elaborated on either their affirmation- or a control exercise with the help of a teaching assistant. We also examined whether values affirmation affected the level of problem behavior of negatively stereotyped ethnic minority youth. Contrary to what was expected, multilevel analyses revealed that the intervention had no effect on the school achievement or the problem behavior of the ethnic minority students. Possible explanations for these findings, mainly related to contextual and cultural differences between the Netherlands and the US, are discussed.